Pengaruh Faktor Fundamental dan Ekonomi Makro terhadap Harga Saham - Sinaga, Ari Kristanti; Triaryati, Nyoman (E-Jurnal Manajemen; Vol 3 No 5 (2014), 2014)
The stock price is the price of a stock at a certain time that happened in the stock market . The stock price can reflect the value of a company . Purpose of study was to determine the influence of fundamental factors proxied by return on equity (ROE) , debt to equity ratio (DER) and price-to -book value (PBV) , as well as factors macroeconomic proxied by inflation and gross domestic product (GDP) in the property and real estate companies in Indonesia Stock Exchange , the period 2008-2012 . The research data is secondary data from the annual financial statements of the company. Hypothesis testing using multiple linear regression analysis using SPSS 16 for windows . The results of this study is return on equity (ROE) and price-to -book value (PBV) have a significant positive effect on stock prices , while the debt-to- equity ratio (DER) , inflation and gross domestic product (GDP) had no effect on stock prices . Simultaneously, five variables have a significant effect on stock prices. Keywords : stock price , ROE , DER , PBV , Inflation , GDP